Laparoscopic pyeloplasty for newborns with severe hydronephrosis - Shi, Tong; Lao, Weihua; Ouyang, Keyu; Chen, Yueqing; Zhang, Yikui; Luo, Jiayao; Chen, Shuhan (Frontiers in Pediatrics, 2024)
Aim: We aimed to investigate the short-term efficacy and safety of laparoscopic pyeloplasty for treating newborns with severe hydronephrosis due to ureteropelvic junction obstruction (UPJO). Methods: A retrospective analysis was performed on 16 newborn patients with severe neonatal hydronephrosis who underwent laparoscopic pyeloplasty at our hospital from January 2021 to November 2022. All patients were regularly followed up. Laparoscopic pyeloplasty with double J stent placement was performed after the presence of severe hydronephrosis was confirmed. Results: Among the 16 pediatric patients (13 males, 3 females), the left side was affected in 13 cases and the right side in 3. The average age at surgery was 9.50 (8.50-12.00) days, with an average weight of 3.30±0.95 kg. Laparoscopic pyeloplasty was performed in all cases without the need for open conversion. The mean surgery duration was 292.06±73.60 minutes, with minimal blood loss (2.50, 2.00-5.00 ml). Postoperative hospital stays averaged 13.44±4.70 days. No anastomotic leakage occurred, and follow-ups at 1, 3, 6, and 12 months showed no stent displacement, except for one case where the stent was removed at 1 month, and the others at 3 months. There were no cases of worsened hydronephrosis, except for one with renal atrophy at the 6-month follow-up. Changes in renal pelvis anteroposterior diameter exhibited a time effect (F=49.281, P<0.001), with significant differences at 1, 3, 6, and 12 months postoperatively compared to preoperative values (P<0.05). Notably, differences were observed between 6 and 3 months, as well as between 12 and 3 months postoperatively (P<0.05). Similarly, renal parenchymal thickness changes showed a time effect Pediatric urology, Guangdong Women and Children Hospital, Guangzhou, China (F=49.281, P<0.001), with significant differences at 1, 3, 6, and 12 months postoperatively compared to preoperative values (P<0.05). Significant differences were also noted between 6 and 1 month, as well as between 12 and 1 month postoperatively (P<0.05). There was one case of urinary tract infection after surgery, and no case of recurrence was observed. Conclusion: Severe neonatal hydronephrosis must be treated promptly. Laparoscopic pyeloplasty is a safe and feasible treatment with minimal complications for newborn patients with severe hydronephrosis due to UPJO.